Gemcitabine and docetaxel for metastatic soft tissue sarcoma: a single center experience - Schmitt, Thomas; Kosely, Florentina; Wuchter, Patrick; Schmier, Johann-Wilhelm Adam; Ho, Anthony Dick; Egerer, Gerlinde (Onkologie, 2013)
Background: Prognosis and survival for patients with metastatic soft tissue sarcoma (STS) are dismal. Standard first-line systemic chemotherapy is anthracycline-based. Gemcitabine/docetaxel (GD) is a therapeutic option in the second-line setting. Here we present the data of our single center retrospective analysis, using GD in locally advanced or metastatic disease. Patients and Methods: Between 2005 and 2012, a total of 34 patients were identified. The majority of tumors were located in the extremities (19/34, 56%) and abdomen/retroperitoneum (10/34, 29%). Most frequent histologies included leiomyosarcoma (13/34, 38%), liposarcoma (7/34, 21%), and pleomorphic sarcoma (6/34, 18%). Results: Objective response to treatment by RECIST criteria after 3 cycles was low with 6% partial responses (PR, 2/34), 65% stable disease (SD, 22/34), and 29% progressive disease (PD, 10/34). Progression-free survival at 3 and 6 months was 77 and 62%, respectively. Patients with a clinical benefit (defined as PR or SD after the 3rd treatment cycle) had a significantly prolonged median progression-free and overall survival with 8.6 months (p < 0.0001; hazard ratio (HR) 33.1) and 22.4 months (p < 0.0001; HR 12.9), respectively. Most common toxicities included hand-foot syndrome, edema, pancytopenia, febrile neutropenia, and mucositis. Conclusion: Overall, we conclude that GD is an active second-line regimen in metastatic STS, with manageable side effects.